2016
DOI: 10.1016/j.jclinane.2016.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety of hydroxypropyl-β-cyclodextrin–diclofenac in the management of acute postsurgical pain: a pooled analysis of 2 randomized, double-blind, placebo- and active comparator–controlled phase III clinical trials

Abstract: Although a longer duration follow-up study in a larger patient population would expand our understanding of potential CV risks, the present analysis suggests that postoperative use of HPβCD-diclofenac does not present an added CV safety risk over placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The age-stratified data from the current analysis support and expand upon the observations reported in the three previous pooled analyses of bleeding, renal, and cardiovascular AEs in the two double-blind trials of HPβCD-diclofenac by also including a large number of patients from the open-label trial, which included large numbers of at-risk patients in an attempt to more accurately reflect real-world practice [ 10 – 12 ]. The current analysis found that the relative risks of bleeding AEs, compared with placebo, in patients receiving HPβCD-diclofenac and aged 65–74 or ≥ 75 years were similar to the risk in those aged < 65 years, and the risks in all three age groups were not significantly different from placebo.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The age-stratified data from the current analysis support and expand upon the observations reported in the three previous pooled analyses of bleeding, renal, and cardiovascular AEs in the two double-blind trials of HPβCD-diclofenac by also including a large number of patients from the open-label trial, which included large numbers of at-risk patients in an attempt to more accurately reflect real-world practice [ 10 – 12 ]. The current analysis found that the relative risks of bleeding AEs, compared with placebo, in patients receiving HPβCD-diclofenac and aged 65–74 or ≥ 75 years were similar to the risk in those aged < 65 years, and the risks in all three age groups were not significantly different from placebo.…”
Section: Discussionsupporting
confidence: 75%
“…Safety considerations relating to the use of NSAIDs include the potential for adverse gastrointestinal, cardiovascular, bleeding, and renal events, which can limit the suitability of this class in at-risk groups such as older patients and those with pre-existing renal and/or hepatic insufficiency [ 7 9 ]. Three previous pooled analyses of safety data from two phase III, parallel-group trials comparing HPβCD-diclofenac with placebo and ketorolac, another injectable NSAID, in patients with acute moderate-to-severe postoperative pain did not show a higher relative risk for bleeding [ 10 ], renal [ 11 ], or cardiovascular adverse events (AEs) [ 12 ] among patients receiving HPβCD-diclofenac or ketorolac compared with placebo. However, surgical procedures in older patients at increased risk of the AEs typically associated with the use of NSAIDs are becoming increasingly common and this has led to a commensurate increase in the use of postoperative analgesia in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Patient disposition for the pooled population has been previously reported in Gan et al44 In total, 608 surgical patients were included in the analysis (HPβCD-diclofenac: n=318; ketorolac: n=142; placebo: n=148). Within the HPβCD-diclofenac group, n=132 patients received HPβCD-diclofenac 18.75 mg, n=150 received HPβCD-diclofenac 37.5 mg, and n=36 received HPβCD-diclofenac 50 mg.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is corroborated with studies addressing the ulcerogenic potential of NSAIDs complexed with cyclodextrins, which showed that complexation with either β-CD or HP-β-CD significantly reduced gastric ulcer formation in rats treated with indomethacin or piroxicam, as shown in Table 2. Additionally, a clinical study conducted by Gan et al [38] demonstrated the cardiovascular safety of intravenous HP-β-CD-diclofenac. On the other hand, β-CD significantly enhanced the solubility of sulindac but had no protective effect against gastric ulcer formation in rats [101].…”
Section: Discussionmentioning
confidence: 99%
“…Gan et al, 2016 [38] Diclofenac/HP-β-CD Examined the efficacy and cardiovascular safety of intravenous HP-β-CD-diclofenac (clinical study).…”
Section: Samal Et Al 2012 [29]mentioning
confidence: 99%